Answer: OPTION C.
Step-by-step explanation:
In order to solve the given exercise, you can follow these steps:
1. Given the following function f(x):
![f(x)=\frac{x-2}{3}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cfrac%7Bx-2%7D%7B3%7D)
You must substitute
into the function f(x). Then:
![f(2)=\frac{(2)-2}{3}](https://tex.z-dn.net/?f=f%282%29%3D%5Cfrac%7B%282%29-2%7D%7B3%7D)
2. Evaluating, you get:
![f(2)=\frac{0}{3}\\\\f(2)=0](https://tex.z-dn.net/?f=f%282%29%3D%5Cfrac%7B0%7D%7B3%7D%5C%5C%5C%5Cf%282%29%3D0)
3. Now, the next step is to substitute
into the function g(x):
![g (x) = 3x+2\\\\g (f(2)) = 3(0)+2](https://tex.z-dn.net/?f=g%20%28x%29%20%3D%203x%2B2%5C%5C%5C%5Cg%20%28f%282%29%29%20%3D%203%280%29%2B2)
4. Finally, evaluating, you get the following result:
![g (f(2)) = 0+2\\\\g (f(2)) =2](https://tex.z-dn.net/?f=g%20%28f%282%29%29%20%3D%200%2B2%5C%5C%5C%5Cg%20%28f%282%29%29%20%3D2)
You can identify that it matches with the Option C.
1. 60,30,90 right triangle. y will be hypotenuse/2, x will be
hypotenuse*sqrt(3)/2. So x = 16*sqrt(3)/2 = 8*sqrt(3), approximately 13.85640646
y = 16/2 = 8
2. 45,45,90 right triangle (2 legs are equal length and you have a right angle).
X and Y will be the same length and that will be hypotenuse * sqrt(2)/2. So
x = y = 8*sqrt(2) * sqrt(2)/2 = 8*2/2 = 8
3. Just a right triangle with both legs of known length. Use the Pythagorean theorem
x = sqrt(12^2 + 5^2) = sqrt(144 + 25) = sqrt(169) = 13
4. Another right triangle with 1 leg and the hypotenuse known. Pythagorean theorem again.
y = sqrt(1000^2 - 600^2) = sqrt(1000000 - 360000) = sqrt(640000) = 800 5. A 45,45,90 right triangle. One leg known. The other leg will have the same length as the known leg and the hypotenuse can be discovered with the Pythagorean theorem. x = 6. y = sqrt(6^2 + 6^2) = sqrt(36+36) = sqrt(72) = sqrt(2 * 36) = 6*sqrt(2), approximately 8.485281374
6. Another 45,45,90 triangle with the hypotenuse known. Both unknown legs will have the same length. And Pythagorean theorem will be helpful.
x = y.
12^2 = x^2 + y^2
12^2 = x^2 + x^2
12^2 = 2x^2
144 = 2x^2
72 = x^2
sqrt(72) = x
6*sqrt(2) = x
x is approximately 8.485281374
7. A 30,60,90 right triangle with the short leg known. The hypotenuse will be twice the length of the short leg and the remaining leg can be determined using the Pythagorean theorem.
y = 11*2 = 22.
x = sqrt(22^2 - 11^2) = sqrt(484 - 121) = sqrt(363) = sqrt(121 * 3) = 11*sqrt(3). Approximately 19.05255888
8. A 30,60,90 right triangle with long leg known. Can either have fact that in that triangle, the legs have the ratio of 1:sqrt(3):2, or you can use the Pythagorean theorem. In this case, I'll use the 1:2 ratio between the unknown leg and the hypotenuse along with the Pythagorean theorem.
x = 2y
y^2 = x^2 - (22.5*sqrt(3))^2
y^2 = (2y)^2 - (22.5*sqrt(3))^2
y^2 = 4y^2 - 1518.75
-3y^2 = - 1518.75
y^2 = 506.25 = 2025/4
y = sqrt(2025/4) = sqrt(2025)/sqrt(4) = 45/2
Therefore:
y = 22.5
x = 2*y = 2*22.5 = 45
9. Just a generic right triangle with 2 known legs. Use the Pythagorean theorem.
x = sqrt(16^2 + 30^2) = sqrt(256 + 900) = sqrt(1156) = 34
10. Another right triangle, another use of the Pythagorean theorem.
x = sqrt(50^2 - 14^2) = sqrt(2500 - 196) = sqrt(2304) = 48
-4 is greater than - 10 because -4 is closer to 0 than -10 is
Answer:
75p²
Step-by-step explanation:
Given data
We are given the expression
(196p²– 121p²)
We can see the p is common in both terms
=p²(196-121)
=p²(75)
=75p²
Hence the factorized form is 75p²